Գևորգ Ջահուկյանի կյանքը և գիտական գործունեությունը - Մերի Սարգսյան (ՀՀ ԳԱԱ հրատ.)
Академик Национальной академии наук Республики Армения, заслуженный деятель науки, лауреат государственной премии Республики Армения, доктор филологических наук, профессор Геворк Джаукян родился в 1920 году в селе Шахназар (ныне село Мецаван Лорийской области). Г. Джаукян был одним из лучших лингвистов своего времени. Academician of the National Academy of Sciences of the Republic of Armenia, honored scientist, laureate of the state rize of the Republic of Armenia, Doctor of Philological Sciences, Professor Gevorg Jahukyan was born in the village Shahnazar in 1920 (now the village Metsavan of Lori Province). G. Jahukyan was one of the best linguists of the time.
Keywords: Biography; Auxiliary Sciences of History; Philology; Linguistics; Language and Literature